Power management for internet of everything - Coustans, Mathieu; Dehollain, Catherine (Tutorials in circuits and systems., 2018)
Addresses several advanced topics in the area of Power Management Analog and Mixed-Signal Circuits and Systems. The fundamental aspects of these topics are discussed, and state-of-the-art developments are presented. The book covers subject such as bio-sensors co-integration with nanotechnology.